2020
DOI: 10.3390/catal10010074
|View full text |Cite
|
Sign up to set email alerts
|

Photoreduction of a Pd-Doped Mesoporous TiO2 Photocatalyst for Hydrogen Production under Visible Light

Abstract: Photoreduction with visible light can enhance the photocatalytic activity of TiO2 for the production of hydrogen. In this article, we present a strategy to photoreduce a palladium-doped TiO2 photocatalyst by using near-UV light prior to its utilization. A sol-gel methodology was employed to prepare the photocatalysts with different metal loadings (0.25–5.00 wt% Pd). The structural and morphological characteristics of the synthesized Pd-TiO2 were analyzed by using X-ray Diffraction (XRD), BET Surface Area (SBET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 72 publications
0
31
0
Order By: Relevance
“…However, by impregnating, doping, or co-doping TiO 2 with metals such as iron (Fe), silver (Ag), palladium (Pd) and platinum (Pt) or non-metals like nitrogen (N), one can improve (a) the reduction of the TiO 2 energy band gap (E BG < 3.2 eV), (b) the slowing of the (e − )/(h + ) recombination rate, and (c) the diminishing of the particle agglomeration [17,18]. Furthermore, through the use of a new photocatalyst synthesis utilizing a sol-gel method, larger TiO 2 surface areas (50 m 2 /g < S BET ≤ 150 m 2 /g), morphologies (high porosity) and crystal structures (anatase dominant crystalline phase) can be obtained [11,19]. All these advancements with TiO 2 photocatalysts are extremely important for the improvement of the process of photocatalysis and the extensive application of air treatment, both for VOCs conversion and airborne virus inactivation.…”
Section: Commercial Tio2-based Photocatalystsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, by impregnating, doping, or co-doping TiO 2 with metals such as iron (Fe), silver (Ag), palladium (Pd) and platinum (Pt) or non-metals like nitrogen (N), one can improve (a) the reduction of the TiO 2 energy band gap (E BG < 3.2 eV), (b) the slowing of the (e − )/(h + ) recombination rate, and (c) the diminishing of the particle agglomeration [17,18]. Furthermore, through the use of a new photocatalyst synthesis utilizing a sol-gel method, larger TiO 2 surface areas (50 m 2 /g < S BET ≤ 150 m 2 /g), morphologies (high porosity) and crystal structures (anatase dominant crystalline phase) can be obtained [11,19]. All these advancements with TiO 2 photocatalysts are extremely important for the improvement of the process of photocatalysis and the extensive application of air treatment, both for VOCs conversion and airborne virus inactivation.…”
Section: Commercial Tio2-based Photocatalystsmentioning
confidence: 99%
“…This allows numerical simulations for different reactor configurations and conditions relevant to industrial-scale applications [9,[35][36][37]. It can be anticipated that CFD will help to design, develop, and analyze novel photocatalytic reactors (bench or pilot-scale) for air [2,12,14,38] or water treatment applications [39][40][41] and water splitting for hydrogen production [18,19,42].…”
Section: Commercial Tio2-based Photocatalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heterogeneous photocatalysis has proving to be a good alternative. Studies have shown its effectiveness in environmental remediation of contaminated waters (Machado et al, 2008;França et al, 2016;Hurtado, Sader & Delgado, 2019), as well as in hydrogen production (H 2 ), an important energy vector (Bahnemann & Schneider, 2013;Rusinque, Escobedo & Lasa, 2020;Galvão et al, 2019).…”
Section: Introductionmentioning
confidence: 99%